Margrethehåb: A Settlement Site of the Early Middle Ages at Roskilde, Zealand - Christensen, Tom (Journal of Danish Archaeology, 1988)
Margrethehåb: A Settlement Site of the Early Middle Ages at Roskilde, Zealand